Improvement of Cation Exchange Capacity of Natural Zeolite with Alkali Treatments - Eko Hanudin; Bambang Triyatmo (Jurnal Zeolit Indonesia, 2004)
The natural zeolite was treated with alkali (NaOH) solution and heating at 100 oC for 12 and 24 hours. The natural zeolite was collected from Gunungkidul, Jogjakarta, Indonesia. The series of NaOH solutions was 0.5, 1.0, 1.5, 2.5, 3.5 and 4.5 M. The final product of the reaction (precipitate) was designated as 'activated natural zeolite (ANZ)'. The cation exchange capacity (CEC) of the ANZ increased with increasing NaOH concentration up to 1.5-3.5 M. Treatment with NaOH 3.5 M and 12 hours in period of hydrothermal reaction resulted in a maximum CEC (395.6 cmol.kg-1). The maximum CEC also observed for treatment with NaOH 1,5 M, but consumed a longer time (24 hours). The increase in the CEC of the ANZ about 300 % higher than the original one. The XRD (X-ray Diffraction) peaks of the ANZ appear at 2.7, 3.2, 4.1, 5.1, 7.2 Ã…, this indicated a new crystalline matters (possibility phillipsite) present. Electron micrograph showed that the ANZ has a large cubic/prismatic structure with a perfect form.